Broken Cities: A Historical Sociology of Ruins, by Martin Devecka. - Petersen, Andrew (Journal of Islamic Archaeology, 2021)
Broken Cities: A Historical Sociology of Ruins, by Martin Devecka. John Hopkins University Press, 2020. 184pp., $34.95. ISBN-13: 9781421438429.